Foodborne Pathogens On Meat Stored Central Cold Rooms In Ibadan And Their Susceptibility To Antimicrobial Agents (2020)
Foodborne pathogens are the leading cause of illness and death in developing countries and are often associated with poor hygiene and unsafe food storage conditions. Using central cold rooms with alternate power supply in preserving meats due to erratic power supply is common among meat traders in Nigeria. However, the public health safety of the operations of this practice remains un-investigated. We conducted a microbial assessment of aseptically collected meat swabs from three selected major cold rooms in Ibadan for Staphylococcus aureus, Listeria monocytogenes, Salmonella spp. and Escherichia coli using standard procedures. Antibiotic susceptibility was determined using 14 different antibiotics at standard concentrations following Kirby- Bauer Assays. The data were analysed with Stata 12.0 using bivariate and logistic regression analyses. Of 180 meat swabs collected, 42.2 % were positive for S. aureus, 22.2 % for L. monocytogenes, 20.0 % for Salmonella spp. and 6.7 % for E. coli. All of the isolates exhibited total resistance to seven of the antibiotics. Escherichia coli showed the highest resistance to 12 antibiotics, followed by Salmonella spp. (11 antibiotics), L. monocytogenes (10 antibiotics) and S. aureus (7 antibiotics). Sampling locations were significantly associated with the prevalence of L. monocytogenes (P = 0.008) and S. aureus (P = 0.000), but not with Salmonella spp. (P = 0.435) orE. coli (P = 0.117). The study revealed a heavy microbial contamination with major foodborne pathogens characterized by a high level of antibiotic resistance. These findings portend that the current operations associated with the practice of using central cold rooms in meat preservation in Nigeria undermine public health safety and need to be urgently addressed.